A clinical pathway for early diagnosis and initial management of Pott’s puffy tumor in children - Cecilia Banda; Michael Weiss; Maria Pilar Gutierrez; Brandon Chatani; Ivan Alberto Gonzalez; Hector Chavez (Pediatric Emergency Medicine Journal)
Purpose Pott’s puffy tumor (PPT), characterized by frontal bone osteomyelitis and subperiosteal abscess, typically arises as a complication of head trauma or frontal sinusitis and is associated with diverse triggers. Since 2001, PPT, previously considered rare in the pediatric population, has been increasingly reported, underscoring heightened recognition. By outlining specific protocols and guidelines, a clinical pathway (CP) facilitates rapid identification and treatment of PPT. Methods We reviewed 11 cases of PPT in patients aged 0 to 18 years who were either hospitalized or discharged from 2 large hospitals in South Florida, United States, from January 31, 2016 through February 1, 2019. This multicenter retrospective case review was complemented by a comprehensive literature review. Additionally, the study team proposed a diagnostic CP tailored for the emergency department setting. Variables of interest included demographic data, clinical presentation, imaging studies, medical and surgical management details, laboratory/microbiological data, and clinical outcomes. Results A total of 11 patients with PPT were identified, of whom 8 and 7 were boys and African Americans, respectively. The common symptoms were fever, headache, and frontal edema. All patients underwent antibiotic therapy for 6-8 weeks, as well as both computed tomography and magnetic resonance imaging. The imaging studies showed intracranial complications in the 10 patients such as epidural abscess, which were caused by Streptococcus pneumoniae, Streptococcus intermedius, Streptococcus pyogenes, Eikenella spp., and methicillin-sensitive Staphylococcus aureus. The 10 patients underwent endoscopic sinus surgeries, with 6 of them also doing craniotomies. No mortality or sequelae was reported. Conclusion This study contributes to the growing body of literature on PPT, shedding light on its evolving epidemiology, clinical manifestations, and management strategies while emphasizing the pivotal role of emergency physicians for optimal outcomes. The proposed CP aims to establish a standard of care that can be adopted across various pediatric emergency departments.